Study to compare Correlation between Digital Hemoglobin Meter and Hematology Analyzer in Hemoglobin Measurement: (Medical equipment’s description report) - Dr. Jhalak Patel; Dr. Vishwas Amin (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Description of the Device Dolphin Digital Hemoglobin Meter Haemoglobin measurement is widely performed in Blood bank [1] and screening, as Anemia is major health concern in India [2]. Different methods use for haemoglobin estimation like copper sulphate gravimetric method, Hemoglobin colour scale, HICN method, Automated Hematology analyzer, point of care haemoglobin meter etc